Macrophage receptor-mediated recognition, response and treatment of Leishmania major infection - Nelson, Keith G., author; Mason, Gary, advisor; Gentry-Weeks, Claudia, committee member; Zeidner, Nordin, committee member; Bamburg, James, committee member (Colorado State University. Libraries, 2011)
We investigate the role of macrophage receptors in the recognition of Leishmania major and response to the parasite, focusing on complement receptors (CR). CR1 and CR3 are the main complement receptors on murine macrophages, recognizing specific parasite surface antigens and parasites opsonized by complement component 3 (C3). Utilizing C3-deficient mice, we show a clear role for complement in enhancing parasite infectivity, and recognition of and response to L. major by the murine host. In our in vitro experiments blocking CR1 and CR3, there is a clear effect of the route of parasite recognition and entry into the macrophage on parasite phagocytosis and cytokine response to infection by L. major, although Th1/Th2 bias is unaffected by blocking complement receptors. Using parasite strains lacking in the two most common surface molecules of L. major (LPG and gp63), we show a strong role for gp63 in the interaction with C3 and complement receptors, particularly CR3. Lastly, we demonstrate the utility of targeting anti-leishmanial therapeutics in infected hosts to the macrophage through another macrophage receptor, the scavenger receptor.
Keywords: macrophage; nanodisk; complement; gp63; Leishmania